Key terms in pragmatics - Allott, Nicholas (Key terms series., 2010)
Pragmatics is a core discipline within linguistics, but is without an introduction organised by key terms until now. Key Terms In Pragmatics succeeds in tackling this problem by giving students clear, explanatory definitions of over 300 key terms in the field. There are short intellectual biographies of key thinkers, and a list of key works for further reading. This book is essential reading for students on introductory and intermediate courses on linguistics and language and communication, especially those studying pragmatics and logic and meaning. It is also useful to more advanced stu.